Powering the future: Innovations of nitrogen-doped activated carbon-cathode sulfur hosts for high performance lithium-sulfur batteries / Mohd Saufi Md Zaini ... [et al.] - Md Zaini, Mohd Saufi; Roslan, Siti Zaharah; Al-Junid, Syed Mutalib; Syed-Hassan, Syed Shatir A. (2024)
Lithium-sulfur (Li-S) batteries have emerged as a promising solution owing to their high theoretical energy density. However, practical implementation has been hindered by the dissolution of lithium polysulfide (LiP) between electrodes, resulting in decreased discharge capacity performance. Thus, this innovation aims to address this challenge by developing an efficient sulfur-cathode host from nitrogen-doped activated carbon (NDAC) derived from palm kernels for the inhibition of LiP. Through nitrogen heteroatom incorporation, the weak interaction between nonpolar carbon surfaces and polar LiP terminals is enhanced, improving the chemical binding capability. Following the sulfur loading, the sulfur composite cathode (NDAC/S) demonstrated stable electrochemical performance, with an initial discharge capacity of 1054.96 mAh/g at 0.1C and retaining a capacity of 686.52 mAh/g after 100 cycles. This capacity is approximately five times higher than commercial nickel manganese cobalt oxide (NMC) Li-ion batteries, which typically offer 278 mAh/g capacity. Owing to its distinctive porous structure and surface nitrogen functionalization, NDAC/S effectively suppressed the formation of lithium polysulfide, resulting in remarkable electrochemical performance.